2017
DOI: 10.1097/j.pain.0000000000001013
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MRAK009713 is a novel regulator of neuropathic pain in rats

Abstract: Long noncoding RNAs have been implicated in neuropathy. Here, we identify and validate a long noncoding RNA, MRAK009713, as the primary regulator of neuropathic pain in chronic constriction injury (CCI) rats. MRAK009713 expression was markedly increased in CCI rats associated with enhanced pain behaviors, and small interfering RNA against MRAK009713 significantly reduced both mechanical and thermal hyperalgesia in the CCI rats. MRAK009713 is predicted to interact with the nociceptive P2X3 receptor by CatRAPID,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 40 publications
0
66
0
Order By: Relevance
“…Emerging evidence indicates that lncRNAs are deregulated and play important roles in the development of neuropathic pain [4,5]. For example, Li et al [22] reported that lncRNA MRAK009713 expression was markedly increased in CCI rats, and siRNA against MRAK009713 significantly inhibited the nociceptive P2X3 expression and thus reduced both mechanical and thermal hyperalgesia in the CCI rats. Gm14461 was highly expressed in injured DRG 6 days following peripheral nerve injury in mice with neuropathic pain, suggesting the potential involvement of Gm14461 in regulating neuropathic pain [11].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicates that lncRNAs are deregulated and play important roles in the development of neuropathic pain [4,5]. For example, Li et al [22] reported that lncRNA MRAK009713 expression was markedly increased in CCI rats, and siRNA against MRAK009713 significantly inhibited the nociceptive P2X3 expression and thus reduced both mechanical and thermal hyperalgesia in the CCI rats. Gm14461 was highly expressed in injured DRG 6 days following peripheral nerve injury in mice with neuropathic pain, suggesting the potential involvement of Gm14461 in regulating neuropathic pain [11].…”
Section: Discussionmentioning
confidence: 99%
“…Next, the underlying mechanism of GClnc1 was revealed. GClnc1 was mainly located in bladder cancer nuclei, and the catRapid online tool was used to predict the interaction GClnc1 and proteins (39)(40)(41). Results showed that LIN28B can bind to GClnc1 through catRapid prediction.…”
Section: Discussionmentioning
confidence: 99%
“…In Hirschsprung's disease (HSCR), apoptotic neurons can inhibit apoptosis in non-apoptotic cells by secreting extracellular bodies containing high levels of HN12-lncRNA [24]. In chronic compressive injury (CCI), lncRNA MRAK009713 is a major regulator of neuropathic pain in rats and is significantly increased in CCI rats with enhanced pain behavior [25]. Interestingly, abnormal expression of various lncRNAs makes much sense in ischemic brain injury.…”
Section: Discussionmentioning
confidence: 99%